Vaccine Refusals among Malaysian Facebook Users: The Self-Presentation - Wan Mohd Ghazali, Wan Norshira; Idris, Hamidah; Mohamed, Shafizan; Mohd Nasir, Nur Shakira (2021)
Vaccinations have been successful in eradicating infectious diseases like smallpox, diphtheria, and many others. However, the distrust towards vaccines on social media has led to an increase in anti-vaccination sentiment and vaccine hesitancy around the globe, including Malaysia. Facebook is known to provide a space for anti-vaxxers to engage and share distorted or unfounded views about vaccination. However, little data on who are the anti-vaxxers among Malaysian Facebook users. This study aims to identify the types of anti-vaxxers and how they portray themselves on Facebook to engage with other online users. A study was conducted to profile these Facebook users and the information used by them in constructing their online identities. This study only analysed the publicly available content on Facebook which was argued ethically acceptable. A total of 456 Facebook users who claimed to reject vaccines publicly on a selected Facebook page, Malaysia Kene Tahu (MKT), were quantitatively profiled. The results showed that the majority maintained genuine profile accounts using real photos and names. While Facebook allows users to disclose a variety of information, users mainly revealed gender and location which are perceived to enhance the trustworthiness of an online identity. The study argued that personal information disclosure on Facebook could build trust among users to further exchange disapproval towards vaccination and confirm each other’s viewpoints. In conclusion, this study affirmed that Facebook is a platform that nurtures anti-vaccination sentiments. Hence, approaches regulating discussion among Malaysian Facebook users is needed and involvement of different stakeholders is required to address the vaccine hesitancy phenomenon specific to the Malaysian context.